2009
DOI: 10.1159/000238116
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Spina Bifida in the Era of Prenatal Diagnosis and Termination of Pregnancy

Abstract: Objective: To evaluate the current outcome of a selected prenatally diagnosed spina bifida group. Materials andMethods: We analyzed and followed up 74 cases of prenatally diagnosed spina bifida. Results: Termination of pregnancy was chosen in 72% of the cases and 28% were live-born. Chromosomal defects were identified in 16%, although only 1.6% in isolated cases. Of the 21 live births, 3 died in the neonatal period. The other 18 (86%) were all alive after an average follow-up of 3 years and 6 months (range 5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…We identified 15 articles meeting inclusion criteria using the search strategy (Harmon et al, 1995;Forrester and Merz, 2000;Waller et al, 2000;Olde Scholtenhuis et al, 2003;Biggio et al, 2004;Garne et al, 2005;Ghi et al, 2006;Nikkila et al, 2006;Tairou et al, 2006;Poretti et al, 2008;Aguilera et al, 2009;Amari et al, 2010;Lu et al, 2011;Machado et al, 2012). One additional article was found using Google Scholar (this article had cited one of the articles identified using the search strategy) (Adama van and one article was known to the authors and included (Shulman et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 15 articles meeting inclusion criteria using the search strategy (Harmon et al, 1995;Forrester and Merz, 2000;Waller et al, 2000;Olde Scholtenhuis et al, 2003;Biggio et al, 2004;Garne et al, 2005;Ghi et al, 2006;Nikkila et al, 2006;Tairou et al, 2006;Poretti et al, 2008;Aguilera et al, 2009;Amari et al, 2010;Lu et al, 2011;Machado et al, 2012). One additional article was found using Google Scholar (this article had cited one of the articles identified using the search strategy) (Adama van and one article was known to the authors and included (Shulman et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…They found 67% correct matching, and the assigned lesion levels were all within two segments. Aguilera et al [1 ]also reported the results in a regionally grouped fashion of 74 cases that underwent 2D examination. Correct matching was observed in 61% of cases, and the remaining cases had lesion levels that were within two segments.…”
Section: Discussionmentioning
confidence: 99%
“…Information given during prenatal diagnosis will usually direct the families to decide upon medical abortion. In a retrospective analysis of fetuses with spina bifida diagnosed in the last 10 years, nearly 3/4 of families opted for medical abortion [1]. Bruner and Tulipan [2] stated that, contrary to general beliefs, the prognosis is not always catastrophic for these infants.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent publication from the UK followed 74 cases of prenatally diagnosed spina bifida. Termination of pregnancy was elected in 72% of the cases [8]. …”
Section: Mmc: Our Evolving Understandingmentioning
confidence: 99%
“…Prenatal selection as well as improved perinatal medical and surgical care have improved neurological outcome [8]. Recent published reports with long-term outcomes at several decades reveal that the clinical outcome for patients with MMC treated in a nonselective manner is extremely variable, ranging from severe cognitive and motor disability to near normal neurological status.…”
Section: The Protocol: An Evidence-based Analysismentioning
confidence: 99%